Possibilities of using rheological parameters as physical indicators of soil structural changes - V. V. Klyueva; D. D. Khaydapova (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
The rheological parameters of structured soddy-podzolic soils (Albic Glossic Retisols (Lomic, Cutanic)) and chernozems (Haplic Chernozems (Loamic, Pachic)) in their natural state and involved in agricultural use were studied by the oscillation amplitude sweep test. Shear resistance parameters of the studied soils (shear stress at the end of the linear viscoelasticity range – LVE-range tL, shear stress tF at the Crossover point and maximum shear stress tmax) were more informative and indicated pronounced differences between soil genetic horizons in contrast to viscoelasticity parameters (deformation γL at the end of the LVE-range and the integral zone Z) when comparing natural and arable soils. The agricultural land use resulted in decreased organic carbon content and, as a consequence, reduced viscoelasticity and shear resistance of the soils. At the same time, the higher bulk density of arable horizons and the redistribution of fine soil particles (physical clay) could explain maximal values of the rheological parameters in the upper arable horizons and their slight differentiation with depth. Further development in the application of the proposed and studied rheological parameters can give insight into the nature and strength evaluation of interparticle bonds, the soil processes under the impact of agricultural machinery, and can also be integrated into the system of physical indicators of soil structural changes.